Obstacles to Early Diagnosis and Treatment of Hidradenitis Suppurativa: Current Perspectives on Improving Clinical Management - Snyder CL; Chen SX; Porter ML (Dove Medical Press, 2023)
Corey L Snyder,1,2 Stella X Chen,1,3 Martina L Porter1,4 1Clinical Laboratory for Epidemiology and Applied Research in Skin (CLEARS), Department of Dermatology, Beth Israel Deaconess Medical Center, Boston, MA, USA; 2Department of Dermatology, University of Texas Southwestern Medical School, Dallas, TX, USA; 3Department of Dermatology, Massachusetts General Hospital, Harvard Combined Dermatology Residency Program, Boston, MA, USA; 4Department of Dermatology, Beth Israel Deaconess Medical Center, Boston, MA, USACorrespondence: Martina L Porter, Department of Dermatology, Beth Israel Deaconess Medical Center, 330 Brookline Avenue, Dermatology Research GZ 522, Boston, MA, 02215, USA, Tel +1-617-667-5834, Fax +1-617-667-4980, Email mporter3@bidmc.harvard.eduAbstract: Hidradenitis suppurativa (HS) is a chronic inflammatory skin condition that can progress to significant tunnels and scars that affect quality of life, especially if diagnosis and treatment are delayed. Average delay after initial presentation of HS symptoms can range from 3 to 10 years in adults and 1 to 2 years in children. Factors associated with diagnostic delay include female gender, non-white race, and greater disease severity at diagnosis. Contributing factors include misdiagnoses, difficulty accessing a dermatologist, hesitation in seeking care due to the stigmatizing nature of the disease, and lack of awareness among providers and patients. While efforts to increase awareness include academic talks at conferences and by foundations geared toward HS, social media offers the opportunity to reach young audiences. Many patients report dissatisfaction with their HS treatments. Better understanding of HS pathophysiology and implementation of clinically focused phenotypes and endotypes can lead to development of more targeted and efficacious therapies. FDA approval of medications for HS beyond adalimumab will increase access to a wider selection of therapies, and implementation of therapeutic drug monitoring may maximize the use of biologics for HS.Keywords: hidradenitis suppurativa, acne inversa, diagnosis, delayed diagnosis, therapeutics, time-to-treatment